Bessas – kariera Ostrogota w Bizancjum - Wolińska, Teresa (Acta Universitatis Lodziensis. Folia Historica, 2005)
Among the commanders of Justinian I of barbarian origin, Bessas was the one who certainly deserves special attention. He was born in Thrace, ca. 480 AD. His ethnicity is controversial because of contradictions in sources (Procopius, Jordanes). He was most likely of Gothic origin, which a Russian scholar E. C. Skshinskaya tried to prove in a convincing way. Bessas descended from the Ostrogoths who did not leave for Italy along with Theodoric Amal in 488. The family of Bessas was assimilated, still they did not forget their mother tongue. Bessas’ military career started early. During the reign of Anastasius (503 AD) he had fought in the Roman army against Persians. Then, under Justinian he continued his service in the East in Arzacene and Martyropolis. It was then that he showed his military talent, but it was also then that he was accused for the first time of private grabbing. In 535-540 he accompanied Belisarius in Sicily where he fought with his kinsmen. He took part in the siege of Naples (he was to negotiate the conditions of surrender in his native language), Nami campaign and commanded the defense of Rome. On that last post he showed both much personal courage and little farsightedness. It was then that the beginning of the conflict between him and Belisarius could be observed, and this was not even soothed by the fact of saving the life of the latter by Bessas. Later we shall find Bessas on the side of Belisarius’ rival, Narzes. When Belisarius was called away from Italy, Bessas remained there but without any significant military success. With Belisarius’ return to Italy (spring 545), Bessas took over the command of the garrison of Rome. Procopius accuses him of taking this opportunity to multiply his fortune, which he eventually lost when the Goths captured the city. According to the writer, Bessas was to be so engaged in collecting goods that he did not care for defense of city walls nor did he give support to the defenders. He would not pay enough attention to the rebelious spirits of his men and therefore did not prevent the downfall of Rome. After that he managed to escape and thus avoided captivity. It is not known what he was doing then, until 549 or early 550, when he was appointed magister militum of Armenia. He waged a war against the Abasgi, who were seeking agreement with the Persians and he defended Lasica from the latter. He was famous for the capture of Petra in 551. Alas, again according to Procopius he soon himself wasted the fruits of his victory, as he cared for contributions from the occupied territories rather than for blocking of the passages from Georgia, which enabled a raid of Persian commander, Mermeroes. Following further adversities, Bessas was deprived of command and property and sent to Abkhasia. Although we often read of the wealth he collected, nothing particular can be said about it. Bessas’ career was typical of his times. He chose a military career, which is not strange, because a civilian one would require good education he most probably lacked. Just like many other barbarian chiefs he saw his chance in the service for the Empire and decided to cut off his tribal ties. Although he did not forget his native language, he never hesitated to fight against his kinsmen and never tried to go on their side. Bessas’ estimation is unequivocal. He was certainly a brave soldier and successful commander. On the other hand many sources inform of him as a person who cared mainly for his personal profit even at the cost of his duties. This opinion, however exaggerated, must contain some truth. Although written by a historian who did not have the reasons to like a soldier opposing his favorite Belisarius, yet his opinion is confirmed to some extent by Agatias and Zacharias the Retor.